Analisis Pengaruh Number of Cycles terhadap Pengujian Durability Slake Batulempung pada Formasi Balikpapan dan Formasi Kampung Baru Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Muhammad Ashar Alias Suara; Tommy Trides; Rety Winonazada; Revia Oktaviani; Windhu Nugroho; Lucia Litha Respati; Henny Magdalena (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Durability is defined as a measure of a rock's resistance to weathering and disintegration when the rock undergoes weathering processes over a short period of time. The susceptibility of rocks to disintegration is related to their low durability. Rock durability is often measured using the slake durability test. The slake durability test is widely used to assess physical changes resulting from wetting-drying processes (Franklin and Chandra, 1972). Therefore, slake durability testing is conducted to understand the weathering of rocks caused by heat and water, particularly clay stones which are one of the constituent rocks on a slope. The sampling location is around Sanga-sanga and Muara Badak. Sampling was conducted with coordinate points and the Balikpapan and Kampungbaru formations. The claystone samples taken were then brought to the Mineral and Coal Technology Laboratory of the Engineering Faculty of Mulawarman University for Slake Durability tests. In this study, the lowest index value obtained was 45.7% and the highest value was 93%, indicating high to very high durability. The difference in the durability index values of claystone at the research locations indicates the presence of variables that can affect the slake durability index values of the claystone in the Balikpapan and Kampungbaru formations, including grain size and mineral content as well as geological conditions at the research site. Based on the results of the claystone durability tests, the durability index value (Id2) was obtained, indicating that the sandstone at the research location falls into the classification of high to low.